(untitled) (Journal of the College of Education for Women, 2019)
The Bajilian had their important part in the first civilian war betweenMuslims. Whether they were against the Umayyad caliphate or with it, whowere small in number, but they had their important part in that actions.The Bajilian who were against the umayyad caliphate had an importantrole in the fall of Umayyad monarchy.The tribe connections between the bajilians were stronger than theirpolitical differences, which had influnces in that time. The bajilians who werein muawiya palace were a good diffencer for the bajilian who were in the sideof the caliph ali. They managed to be their medicater in the muawiya palace. There were big efforts giving by others in order to decrease the bajilianefforts in conquering Iraq and the east. That made bajilia realizing that thecaliphate treated them injustly, that made the bajilian feeling angry against therightly guided caliphs and the umayyad caliphate that made this tribe to bewith the opposition partys against the caliphs.